Patterns of Gender-Based Violence in Conflict-Affected Ukraine: A Descriptive Analysis of Internally Displaced and Local Women Receiving Psychosocial Services - Capasso, Ariadna (Journal of interpersonal violence, 2022)
Since 2014, a protracted armed conflict has afflicted eastern Ukraine, resulting in the displacement of over 1.4 million residents. The resulting humanitarian crisis has placed women, particularly displaced women, at greater risk of gender-based violence (GBV). In Ukraine, reports of GBV were higher following the start of the conflict (22.4% in 2014 vs. 18.3% in 2007), with displaced women suffering from GBV nearly three times more than non-displaced residents (15.2% vs. 5.3%). Many GBV incidents in Ukraine have been reported along the ?contact line,? the border separating government from non-government-controlled areas. This study compares types of GBV experienced by displaced and local (non-displaced) women receiving psychosocial support in order to identify the gaps in services during a time of conflict. Data was collected by mental healthcare providers from 11,826 women (25.5% displaced; 74.5% local) aged 15 to 69 receiving psychosocial services in five conflict-affected regions from February 2016 to June 2017. Group differences were assessed using Pearson?s chi-squared or Fisher?s exact tests for categorical variables and Wilcoxon rank-sum tests for continuous variables. Overall, almost half of the women experienced intimate partner violence and psychological abuse. Compared to residents, displaced women were more likely to report non-domestic GBV incidents involving sexual and economic violence. Almost 8% of violent incidents against displaced women occurred at checkpoints or at reception centers for internally displaced persons (IDP) and 20% were perpetrated by armed men. Consistent with the literature, this study suggests that displaced women are more vulnerable to attacks by persons outside the home and by armed groups. Our findings underscore the need to expand violence prevention programs to address the unique vulnerabilities of displaced women before, during, and after displacement. Programs should be tailored to prevent violence within and outside the home. Increased prevention efforts are needed in areas with high concentrations of armed men, along the contact line, and at IDP reception centers to protect displaced women. This is particularly urgent in the context of increased GBV due to COVID-19.